The impact of educational mismatch on returns to R&D: evidence from manufacturing in OECD countries. Issue 5 (4th July 2019) - Igna, Ioana A.; Venturini, Francesco
ABSTRACT: This paper investigates the effect of educational mismatch of R&D workers on firm's returns to innovation. R&D labour mismatch emerges when R&D workers have competencies different from those required by their occupation providing a contribution to innovation lower than in the case of perfect educational matching. By estimating a knowledge production function on data for 13 manufacturing industries from 16 OECD countries between 2003 and 2011, we find that R&D labour mismatch may cause returns to R&D investment to be between 10 and 15% lower than estimated in the literature. These results are robust to controlling for institutional factors, simultaneity feedbacks and other mis-specification issues. The detrimental effect of the misallocation of R&D labour is found to be stronger in those sectors where R&D activities have greater potential (returns), i.e. high-tech sectors.